FURADAN EFFECT UPON HISTOPATHOLOGY OF OVARY IN THE FRESHWATER FISH Channa punctatus (Bloch) - ., Tulika (The Scientific Temper, 2018)
The furadan exposure with sub-lethal concentration affects upon ovary of freshwater fish, Channa punctatus were investigated. There ovary morphology and anatomy changed in minor and major exposure resulted as reduction in size of mature oocytes, disruption, vacuolization in cytoplasm in acute and complete loss of normal configuration of ovary, necrosis, elongated ovarian follicles, and fragmented ova with abnormal shape under chronic exposures during chronic exposures observed during study period.